Synergy of Aesthetics and Professionalism: Integration of Artistic and Value Orientations Into the University Educational Process - Qing, Liu (Theoretical and Methodical Problems of Children and Youth Education, 2025)
The relevance of the study is determined by the increasing importance of aesthetic competence as an integral component of professional education in universities. Modern higher education emphasizes the need to cultivate students who possess not only specialized knowledge and technical skills but also cultural literacy, aesthetic sensitivity, and ethical awareness. The article explores the essence of integrating artistic and value orientations into the educational process as a means of forming aesthetic competence, highlighting its role in fostering creativity, critical thinking, and holistic personal development. The purpose of the study is to analyze theoretical and practical approaches to the formation of aesthetic competence among university students in the study of professional disciplines and to propose methods for its systematic development.The research employed a combination of theoretical analysis, pedagogical observation, and qualitative assessment methods to examine the mechanisms and effectiveness of aesthetic integration in higher education. The results indicate that incorporating artistic elements into professional training enhances students’ engagement, reflective thinking, and professional readiness while simultaneously promoting the internalization of cultural and value-based norms. The study demonstrates that participatory, project-based, and integrative pedagogical approaches contribute significantly to the development of students’ aesthetic competence. The scientific novelty of the work lies in conceptualizing aesthetic competence as a multidimensional construct encompassing cognitive, emotional, and value-oriented components, and in identifying pedagogical strategies for its systematic development within professional disciplines.The findings can be applied in curriculum design, teaching methodologies, and institutional strategies for higher education institutions seeking to develop ethically aware, culturally competent, and aesthetically sensitive graduates. The study contributes to the theoretical and practical discourse on aesthetic education and provides actionable recommendations for educators aiming to harmonize professional skills development with aesthetic and value-based education.